Using “Book Creator” Application in Making e-Modules as Teaching Material for English TOEFL Courses - Fitria, Tira Nur (International Journal of Computer and Information System (IJCIS), 2024)
This study simulates the use of Book Creator application in making and designing e-module of the material TOEFL courses. This research is descriptive qualitative research. The result analysis shows that e-module can be created in Book Creator. We can open Chrome browser then type book creator.com on the search page. If the book creator has opened, click Create Free Account. We click “New Book”. The e-book size display will appear. The first page (cover) of e-book will be opened. On the right side of the cover there is a “+”, “i” icon and a triangular-shaped play icon. Next select the “+” icon and click “shapes” to create a second color background on the e-book page. We can select the “+” icon to add content to the page. We can select "media" then "import". We will take the contents of the files contained in the device then select the file. The selected file will appear on the e-book page. To add other content such as text, images or audio, select the “+” icon and the menu list below it. To see the appearance and content of the e-book that we created, we can click the play sign in the upper right corner. To share the e-book link, click the play sign, then click the share button on the menu bar and then specify how we want to share the e-book. Book Creator is a book creation application to make an attractive type of book. Book Creator is a simple tool for creating multimedia digital books in any academic area, from elementary school to college. Create content by combining text, music, video, drawings, photographs, and appsmash, a book will be read in different languages, including word highlighting and page flipping. Publish implies to make a book available for online viewing, download as an ePub file, or print as a PDF. Book Creator can bring creativity to our classroom, assist hesitant writers engage, and enable students to show their learning through books created by teachers and students all across the globe.